Os efeitos socioespaciais das usinas hidrelétricas Amador Aguiar I e II: o assentamento Vida Nova em Uberlândia-MG - Bernardelli, Camila (2012)
This work is part of the research project entitled O Rio Araguari Passo a Passo e os Efeitos Socioespaciais da Construção de Barragens developed at Instituto de Geografia of Universidade Federal de Uberlândia (IG/UFU), funded by Fundação de Amparo à Pesquisa do Estado de Minas Gerais (FAPEMIG). The objective of this research is to analyze the social and spatial effects of the Grandes Projetos de Investimentos in Triângulo Mineiro and Alto Paranaíba, specifically in the Assentamento Vida Nova, located in the influence area of the energy enterprises of Amador Aguiar I and II, created as a compensatory measure to the construction of projects. It was tried to design a theoretical discussion to understand the authors point of view from different areas and clarify the main conceptual elements like, for example, the territory, the cultural identity and others that may contribute to the discussion about the implementation of hydropower plants. The methodology was based on the literature in order to identify and establish indicators that point to prior knowledge about the effects directly linked to the processes of compulsory relocation. Subsequently, field works were made to know the reality experienced by individuals who have been displaced and subsequently installed in Assentamento Vida Nova. According to the testimonies collected during the field works, an overview will be prepared about the rehabilitation and adaptation of these people in their new territory.